2022
DOI: 10.3390/jpm12030462
|View full text |Cite
|
Sign up to set email alerts
|

The Dissimilar Impact in Atrial Substrate Modificationof Left and Right Pulmonary Veins Isolation after Catheter Ablation of Paroxysmal Atrial Fibrillation

Abstract: Since the discovery of pulmonary veins (PVs) as foci of atrial fibrillation (AF), the commonest cardiac arrhythmia, investigation revolves around PVs catheter ablation (CA) results. Notwithstanding, CA process itself is rather neglected. We aim to decompose crucial CA steps: coronary sinus (CS) catheterization and the impact of left and right PVs isolation (LPVI, RPVI), separately. We recruited 40 paroxysmal AF patients undergoing first-time CA and obtained five-minute lead II and bipolar CS recordings during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…This channel varied among patients, but was always the same for one patient at all three time points from which the recordings were obtained. In case all channels showed a high amplitude and clear signals, medial or mid-proximal channels were selected [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This channel varied among patients, but was always the same for one patient at all three time points from which the recordings were obtained. In case all channels showed a high amplitude and clear signals, medial or mid-proximal channels were selected [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since structural changes are connected with the anatomical alteration of the atria, a blanking period of 3 months is typically used in order to safely assess the structural substrate modification [ 7 , 10 ]. Although electrical and functional—related to freedom from AF—modification have been observed as early as one day after CA, electrical substrate modification can in fact be observed even earlier, immediately after the CA procedure [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, they showed that left PVI is the critical part of the CA of PVs for paroxysmal AF patients, significantly altering the P-wave duration, whereas the effect of the CA of PVs on the coronary sinus is less straightforward and is demonstrated to a lesser extent. The authors suggest that other atrial structures may be more indicative of the ablation outcome and should be assessed as alternative references [3].…”
mentioning
confidence: 99%